Pain Reactions during Pulmonary Vein Isolation under Deep Sedation: Cryothermal versus Radiofrequency Ablation. Issue 5 (31st March 2016) - ATTANASIO, PHILIPP; HUEMER, MARTIN; SHOKOR PARWANI, ABDUL; BOLDT, LEIF‐HENDRIK; MÜGGE, ANDREAS; HAVERKAMP, WILHELM; WUTZLER, ALEXANDER
Abstract : Background: Left atrial ablation can be accompanied by discomfort or pain. The purpose of this study was to systematically compare pain reactions during ablation of atrial fibrillation under deep sedation with cryothermal and radiofrequency energy. Methods and Results: Circumferential ablation was performed in patients with atrial fibrillation using either radiofrequency (RF) or cryoenergy. Deep sedation was achieved with a combination of propofol and midazolam. Pain reactions were counted and painful ablation sites located. To determine the severity of the pain reactions a Face, Legs, Activity, Cry, Consolability (FLACC) Behavioral Pain Assessment Scale was used: 79 patients (53 RF‐ vs 26 Cryoablations) were included. A total of 92% of patients treated with RF energy showed ≥1 pain reaction during the procedure compared to only 13% in the cryoenergy group (<0.001). The total number of pain reactions was significantly higher in the RF energy group (3.6 ± 4.7 vs1.3 ± 0.6, P = 0.005). Determination of painful sites was performed in the RF group only. Pain reactions were significantly more often observed during RF application left superior pulmonary vein (LSPV) ostium compared to other left atrial ablation sites (Total FLACC Score 2.8 ± 0.6 LSPV, 1.4 ± 0.4 left inferior pulmonary vein [P = 0.009], 1.4 ± 0.3 right superior pulmonary vein [P = 0.044], 1.1 ± 0.3 right inferior pulmonary vein [P = 0.032]). Conclusions: Our results show that despite deep sedation pain reactions often occur during RF ablation. Knowledge of areas with more frequent pain reactions may help electrophysiologists to reduce pain reactions and related patient movements. Ablation with cryoenergy was significantly less painful compared to ablation with RF energy. Cryoablation therefore may be considered for patients at a higher risk for anesthesia‐related complications.